Laparoscopic partial liver resection for hepatocellular carcinoma arising from Fontan-associated liver disease: a case report - Miku Iwata; Katsunori Sakamoto; Chihiro Ito; Akimasa Sakamoto; Mio Uraoka; Tomoyuki Nagaoka; Kei Tamura; Naotake Funamizu; Akihiro Takai; Kohei Ogawa; Yasutsugu Takada (Surgical Case Reports, 2021)
Abstract Background The Fontan procedure (FP) is a palliative surgery for functional single ventricle. The Fontan circulation maintains pulmonary circulation by a high central venous pressure, leading to chronic congestive liver. The number of patients diagnosed with hepatocellular carcinoma (HCC) arising from liver fibrosis and cirrhosis after FP is increasing. Several reports have described surgical treatment for HCC after FP, but few have described laparoscopic surgery. Case presentation The patient was a 31-year-old man who had undergone the FP for single right ventricle at 3 years. Several liver masses were detected at 30 years. A liver mass in segment 3 showed increasing size concomitant with increasing alpha-fetoprotein concentration, and a solitary HCC 15 mm in diameter was diagnosed. The tumor was located on the liver surface, abutting the origin of the left hepatic vein. Laparoscopic partial liver resection was performed. The postoperative course was uneventful and the patient was discharged on postoperative day 3. The patient remained disease-free on follow-up after 7 months. Conclusions Although we had some concerns, such as difficulty managing general anesthesia and easy venous bleeding due to high central venous pressure, laparoscopic partial liver resection was performed with safe exposure of the left hepatic vein.